Heavy Metal Accumulation and Potential Ecological Risk Assessment of Surface Sediments from Day River Downstream - Thi Trinh, Le; Thi Thu Trang, Kieu; Thanh Trung, Nguyen; Khanh Linh, Nguyen; Tham, Trinh Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4351, 2018)
Abstract: According to the statistics of management agencies, the Nhue - Day river basin system is experiencing an increase in the number of polluted sources and waste water flow from production and living activities. The accumulation of persistent organic substances, heavy metals, etc., in sediments affects the quality of river water and the aquatic living system. In this study, the accumulation of heavy metals in sediments from the Day River downstream was assessed based on potential ecological risk index. Results of the research, All heavy metals were detected in sediment samples with mean concentrations of Cu, Pb, Cd and Cr were range of 15.8 ÷ 82, 6; 13.1 ÷ 72.1; 0,189 ÷ 2,43; 16.1 ÷ 97.3 mg / kg dry weight. The potential ecological risk indexs (RI) for metals were varied from 11.4 to 78.7, show that this area has a low level of risk for heavy-metal. This data can clarify the potential risk level of the area which is the scientific basis for taking solution to control and reduce the sources of environmental pollution of the Nhue - Day river basin system. Keywords: Heavy metal, sediment, potential ecological risk, downstream Day River. References [1] Tổng cục Môi trường (2017), Báo cáo tổng hợp kết quả quan trắc môi trường nước lưu vực sông Nhuệ - Đáy [2] Cruz-Guzman M., Celis R., Hermosín M.C., Koskinen W.C., Nater E.A., Cornejo J. (2006), Heavy metal adsorption by Montmorillonites modified with natural organic cations. Soil Sci. Soc. Am. J. 70, (1), 215. [3] Ding X.G., Ye S.Y., Gao Z.J. (2005), Methods of heavy metal pollution evaluation for offshore sediments, Marine Geol Lett. 21, (8), pp 31- 36. [4] Lars Hakanson (1980), An ecological risk index for aquatic pollution control. A sedimentological approach, Water research. 14 (8), pp. 975-1001. [5] TCVN 6663-15: 2008, Chất lượng nước - Lấy mẫu (ISO 566715: 1999) Phần 15: Hướng dẫn bảo quản và xử lý mẫu bùn và trầm tích, Bộ Khoa học và Công nghệ [6] US - Environmental Protection Agency (1996), EPA 3050B Acid digestion of sediments, sludges and soils. [7] F Ackermann (1980), A procedure for correcting the grain size effect in heavy metal analyses of estuarine and coastal sediment, Environmental Technology, 1(11): pp. 518-527 [8] TCVN 4080:2011 - Chất lượng đất: Phương pháp xác định độ ẩm và hệ số khô kiệt, Bộ Khoa học và Công nghệ [9] Lê Thị Trinh (2017), Đánh giá sự tích lũy và rủi ro sinh thái một số kim loại nặng trong trầm tích cửa sông Hàn, Thành phố Đà Nẵng, Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ,. 33(3), p. 112. [10] Nguyễn Văn Phương, Mai Hương, Nguyễn Thị Huệ (2017), Đánh giá ô nhiễm kim loại nặng (Cu, Pb, Cr) và As trong trầm tích cửa sông Soài Rạp, hệ thống sông Sài Gòn – Đồng Nai, Tạp chí Môi trường – Tổng cục Môi trường [11] Md Saiful Islam, Md Kawser Ahmed, Mohammad Raknuzzaman, Md Habibullah-Al-Mamun, Muhammad Kamrul Islam (2015), Heavy metal pollution in surface water and sediment: a preliminary assessment of an urban river in a developing country, Ecological Indicators. 48, pp. 282-291. [12] Ai jun Wang, Ahmed Kawser , Yong hang Xu , Xiang Ye , Seema Rani and Ke liang Chen (2016), Heavy metal accumulation during the last 30 years in the Karnaphuli River estuary, Chittagong, Bangladesh, Springer Plus, 5(1): p. 2079. [13] Mayuri Chabukdhara, Arvind K Nema (2012), Assessment of heavy metal contamination in Hindon River sediments: a chemometric and geochemical approach, Chemosphere. 87(8), pp. 945-953 [14] Mayank Pandey, Smriti Tripathi, Ashutosh Kumar Pandey, and BD Tripathi, Risk assessment of metal species in sediments of the river Ganga, Catena, 2014. 122: p. 140-149.